2014
DOI: 10.2337/db14-0779
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Reduced Kidney Mass on Liver and Skeletal Muscle Insulin Sensitivity in Obese Mice

Abstract: Reduced kidney mass and/or function may result in multiple metabolic derangements, including insulin resistance. However, underlying mechanisms are poorly understood. Herein, we aimed to determine the impact of reduced kidney mass on glucose metabolism in lean and obese mice. To that end, 7-week-old C57BL/6J mice underwent uninephrectomy (UniNx) or sham operation. After surgery, animals were fed either a chow (standard) diet or a high-fat diet (HFD), and glucose homeostasis was assessed 20 weeks after surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Interestingly we showed that UniNX resulted in anti-inflammatory state in most tissues and this was associated with reduced cytokines in tissues such as liver, kidney and fat pads. Recently, it has been shown that in mouse UniNX models, tissues including fat pads showed a reduced inflammatory state (Sui et al, 2010 ; Chin et al, 2015 ). In our study in contrast, IFNγ and GM-CSF protein levels were increased in the UniNX spleen, suggesting that the increased circulating levels of these cytokines may arise from the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly we showed that UniNX resulted in anti-inflammatory state in most tissues and this was associated with reduced cytokines in tissues such as liver, kidney and fat pads. Recently, it has been shown that in mouse UniNX models, tissues including fat pads showed a reduced inflammatory state (Sui et al, 2010 ; Chin et al, 2015 ). In our study in contrast, IFNγ and GM-CSF protein levels were increased in the UniNX spleen, suggesting that the increased circulating levels of these cytokines may arise from the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SIRT1 and FXR can counter the metabolic syndrome by acting on lipid and glucose metabolism. We and others have recently shown that bile salts and their receptor FXR are modified by UniNX (Penno et al, 2013 ; Gai et al, 2014a , b ; Chin et al, 2015 ). It has also been reported that SIRT1 may regulate FXR activity (Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 97%
“…The area under the curve of disappearing plasma 2‐[1‐ 14 C] deoxyglucose was used together with tissue concentration of phosphorylated 2‐[1‐ 14 C] deoxyglucose to calculate glucose uptake as described previously (Chin et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Glucose clamp studies were performed as previously described (23). Clamps were performed in freely moving mice.…”
Section: Glucose Clamp Studiesmentioning
confidence: 99%